Experimental investigations of drilling temperature of high-energy ultrasonically assisted bone drilling. (March 2019) - Sun, Zhibin; Wang, Yu; Xu, Ke; Zhou, Gang; Liang, Chendi; Qu, Junda
Highlights: A novel bone drilling system was designed to achieve high-energy ultrasonically assisted bone drilling. The drilling temperature was compared with conventional bone drilling. High-energy ultrasonically assisted bone drilling had slightly higher drilling temperature than conventional bone drilling. The thermal effect of ultrasonic vibration was a main reason for this phenomenon. Abstract: Ultrasonically assisted drilling as a new type of bone drilling technology has received increasing attention. However, the vibration energy of existing studies was limited. In this study, a robot-based ultrasonically assisted bone drilling experimental setup was designed, and high-energy ultrasonically assisted bone drilling (vibration frequency=24.1–41 kHz, and vibration amplitude=150–160 µm) was applied to bovine cortical bone to investigate the drilling temperature compared with conventional drilling. The effect of drilling speed on drilling temperature was also studied. The experiment results showed that, compared with the conventional bone drilling, high-energy ultrasonically assisted bone drilling had slightly higher drilling temperature (0.36–0.86 °C), which is in direct contrast to previous reports. We hypothesized that this finding was due to the thermal effect of ultrasonic vibration, which the present study confirmed. Moreover, the drilling temperature increased with higher drilling speed.